Pengaruh Pelayanan dan Fasilitas Pemeriksaan Kesehatan pada Masa Pandemi Covid-19 Terhadap Kenyamanan Penumpang (Studi Kasus pada Bandar Udara Internasional Yogyakarta) - Alma Dwi Mahendra (Jurnal Multidisiplin Madani, 2022)
The world of aviation has experienced an increase in passengers since 2015. However, in 2020 there was a decline in passengers due to the emergence of the Covid-19 virus and resulted in new regulations and policies in services and facilities from the government and the airport. This also happened at Yogyakarta International Airport. This policy was made to meet the requirements of traveling passengers and minimize the spread of the Covid-19 virus. For this reason, the purpose of this study was to determine the effect of health check services and facilities on passenger comfort during the Covid-19 pandemic, partially or simultaneously. This study uses a quantitative method by distributing questionnaires to 100 respondents taken from the population of service users and health examination facilities during the Covid-19 pandemic at Yogyakarta International Airport. Based on the results of the study showed the total variation of passenger comfort with an average of 58.1%.